SOTERIOLOGI MENURUT PAULUS SEBAGAI DASAR TRADISI BAGI PELAKSANAAN PENDIDIKAN AGAMA DALAM KONTEKS PLURALISME DI INDONESIA - Demianus Nataniel (Jurnal Abdiel: Khazanah Pemikiran Teologi, Pendidikan Agama Kristen dan Musik Gereja, 2019)
Ronald H. Cram said “the radical dialogue is an appropriate religious education model in pluralism context”. He contended that the radical dialogue consists of the hospitality principles that goes beyond tolerance. Unfortunately, his argumentations have not been based on the biblical tradition. In this paper, therefore, I would like to propose soteriology of the cross in Paul’s letters as a supporting tenet for implementing the radical dialogue in religious education, especially in Indonesian pluralism context. Based on the principles of soteriology of the cross in Paul’s letters, Christian comunity in Indonesia will be provoked to implement the radical dialogue. In order to clarify how the principles of soteriology of the cross are approprieated with the concept of the radical dialogue, I will delineate an Indonesian pluralism context succintly and an appropriate model of religious education in the context respectively.